A Deliberative Approach to Valuing Capabilities: Assessing and Valuing Changes in the Well-Being of those Close to Patients Receiving Supportive End of Life Care. Issue 3 (3rd July 2022) - Kinghorn, Philip; Canaway, Alastair; Bailey, Cara; Al-Janabi, Hareth; Coast, Joanna
ABSTRACT: Aim: Explore the use of deliberative valuation to elicit relative weights for a set of capabilities identified as being important and relevant to those close to patients receiving supportive care at the end of life. Methods: Focus groups, involving the general UK population ( n  =   38) and policy-makers ( n  =   29) with experience of, and influence on, priorities for end of life care. Public participants completed two valuation tasks (budget pie and visual analogue scale (VAS)) individually, discussed their responses, and then recorded a final (individual) response. Policy-makers completed the VAS tasks in a separate series of focus groups. Quantitative and qualitative analyses of participants' responses are reported. Results: Individual values were aggregated to form relative weights for the capabilities. Capabilities given greatest weighting were "good communication between care providers and close persons" and "practical support for close persons". The quantitative impact of deliberation on weights overall was negligible, but qualitative findings indicated that disclosure of personal experiences did appear to prompt others to consider issues from new perspectives. Discussion: Deliberative valuation was found to be a potentially feasible method for generating weights. However, further consideration needs to be given as to how to optimise recruitment whilst ensuring that participants actively engage with the task.